Discovering the structure of nerve tissue: Part 3: From Jan Evangelista Purkyně to Ludwig Mauthner - Chvátal, Alexandr (Journal of the history of the neurosciences, 2015)
The previous works of Purkyně, Valentin, and Remak showed that the central and peripheral nervous systems contained not only nerve fibers but also cellular elements. The use of microscopes and new fixation techniques enabled them to accurately obtain data on the structure of nerve tissue and consequently in many European universities microscopes started to become widely used in histological and morphological studies. The present review summarizes important discoveries concerning the structure of neural tissue, mostly from vertebrates, during the period from 1838 to 1865. This review describes the discoveries of famous as well as less well-known scholars of the time, who contributed significantly to current understandings about the structure of neural tissue. The period is characterized by the first descriptions of different types of nerve cells and the first attempts of a cytoarchitectonic description of the spinal cord and brain. During the same time, the concept of a neuroglial tissue was introduced, first as a tissue for "gluing" nerve fibers, cells, and blood capillaries into one unit, but later some glial cells were described for the first time. Questions arose as to whether or not cells in ganglia and the central nervous system had the same morphological and functional properties, and whether nerve fibers and cell bodies were interconnected. Microscopic techniques started to be used for the examination of physiological as well as pathological nerve tissues. The overall state of knowledge was just a step away from the emergence of the concept of neurons and glial cells.
Keywords: histologické techniky; Neuroanatomy; History, 20th Century; ganglia; dějiny 20. století; History, 19th Century; Microscopy; centrální nervový systém; mozek; zvířata; Animals; Central Nervous System; Neurons; Histological Techniques; mikroskopie; neuroglie; Medical Illustration; lékařské ilustrace; nervová tkáň; neurony; Ganglia; neuroanatomie; Nerve Tissue; Brain; dějiny 19. století; Neuroglia